Bridge retrofit prioritisation for ageing transportation networks subject to seismic hazards - Rokneddin, Keivan; Ghosh, Jayadipta; Dueñas-Osorio, Leonardo; Padgett, Jamie E. (Structure and infrastructure engineering, 2013)
The deteriorating state of highway bridges is traditionally ignored in estimating the seismic reliability of transportation networks. In this study, the present day seismic reliability of ageing bridges in highway networks is evaluated through a time-dependent seismic fragility analysis of typical bridge classes. An efficient algorithm based on finite-state Markov Chain Monte Carlo simulations is also presented to assess the reliability of large ageing highway bridge networks without the need to simplify the network topology. The criticality of ageing bridges is then assessed through different proposed ranking strategies to arrive at an optimised seismic retrofit prioritisation. A case study on an existing bridge network with 515 bridges in the state of South Carolina, USA reveals striking differences between results of the proposed ranking strategies and those from state-of-the-practice methods. Such differences emphasise the significance of accounting for network-level importance in seismic retrofit programs of ageing transportation networks.